Content of Cytokines in Blood Serum after Rhythmic Cold Effects - Babijchuk, V. G. (Problems of Cryobiology and Cryomedicine, 2007)
As the result of the researches the significant deviations towards the rise of pro-inflammatory cytokines in content of aged people’s blood serum have been revealed. Rhythmic cold effects strongly reduce the content of pro-inflammatory interleukins in blood serum down to normal values in middle-aged and aged people and increase the content of granulocyte colony-forming factor (GCFF), that testifies to stimulating effect of low temperatures on adaptive abilities of immune system and, in particular, of its humoral link.